A review on the dynamics of social recommender systems. (2018) - Shokeen, Jyoti; Rana, Chhavi
With the excessive growth of data over internet, it has become difficult to select relevant items and information. Recommender systems are the essential tools to handle the information overload problem and suggesting relevant items to users. On the other hand, a growing explosion of social networking sites in recent years is influencing different aspects of our life. For many years, recommender systems and social networks have been considered as separate areas. But with time, researchers comprehended the significance of combining them to generate improved results. The integration of social networks into recommender system is called social recommender system. In this paper, we investigate different dynamics of social recommender systems that play a major role in generating effective recommendations. Each dynamic individually enhances the quality of social recommender system but the fusion of these dynamics can produce accurate and most striking recommendations. This paper also discusses the relevant research areas in this field.